الاتجاه العام لأسعار الأسهم المدرجة في سوق دمشق للأوراق المالية وبناء نموذج للتنبؤ بها دراسة تطبيقية على أسهم بنك التجارة والتمويل الدولي باستخدام نماذج أريما ونماذج الانحدار للسلاسل الزمنية - البلخي راتب; قزما جان (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يهدف هذا البحث إلى التعرف على الاتجاه العام لأسعار الأسهم لمصرف التجارة والتمويل الدولي(IBTF) وذلك خلال الفترة الممتدة من بداية انطلاق سوق دمشق للأوراق المالية في آذار 2009 و حتى نهاية شهر شباط عام 2011, و بناء نموذج يساعد على التنبؤ بسعر السهم في الأجل القصير. وقد تم تطبيق الأساليب الإحصائية المتعلقة بالسلاسل الزمنية( نماذج الانحدار للسلاسل الزمنية ونماذج أريما ARIMA)) ، توصلت الدراسة إلى أن أفضل نموذج للتنبؤ المستقبلي بأسعار الأسهم هو نموذج الانحدار من الدرجة الثالثة ونموذج ARIMA(2,0,1) وذلك بناءً على عدة مؤشرات لاختبار جودة النموذجين المذكورين دون الأخذ بعين الاعتبار التغيرات الطارئة والموسمية. This research aims to identify the Genral Trend of prices movements of stocks of IBTF bank listed in Damascus Securities Exchange (DSE) during the period starting from the beginning of Damascus Stock Exchange in March 2009 until the end of February 2011, in order to construct a model helping to predict the future prices of the stock in the short term. Using regression models for time series and ARIMA models, the reseach found that there is an incresing trend in stock prices during this period, and has also concluded that the best model to predict future stock prices is the regression model of the third degree and ARIMA (2,0,1), based on several indicators to test the quality of the model in question without taking into account the emergency and seasonal changes.